Anatomic Fitting of Total Artificial Hearts for In Vivo Evaluation. Issue 8 (5th March 2013) - Gregory, Shaun D.; Loechel, Nicole; Pearcy, Mark J.; Fraser, John; Parnis, Steven; Cohn, William E.; Timms, Daniel
Abstract Successful anatomic fitting of a total artificial heart (TAH) is vital to achieve optimal pump hemodynamics after device implantation. Although many anatomic fitting studies have been completed in humans prior to clinical trials, few reports exist that detail the experience in animals for in vivo device evaluation. Optimal hemodynamics are crucial throughout the in vivo phase to direct design iterations and ultimately validate device performance prior to pivotal human trials. In vivo evaluation in a sheep model allows a realistically sized representation of a smaller patient, for which smaller third‐generation TAHs have the potential to treat. Our study aimed to assess the anatomic fit of a single device rotary TAH in sheep prior to animal trials and to use the data to develop a three‐dimensional, computer‐aided design (CAD)‐operated anatomic fitting tool for future TAH development. Following excision of the native ventricles above the atrio‐ventricular groove, a prototype TAH was inserted within the chest cavity of six sheep (28–40 kg). Adjustable rods representing inlet and outlet conduits were oriented toward the center of each atrial chamber and the great vessels, with conduit lengths and angles recorded for future analysis. A three‐dimensional, CAD‐operated anatomic fitting tool was then developed, based on the results of this study, and used to determine the inflow and outflow conduit orientation of the TAH. The mean diameters of the sheep left atrium, right atrium, aorta, and pulmonary artery were 39, 33, 12, and 11 mm, respectively. The center‐to‐center distance and outer‐edge‐to‐outer‐edge distance between the atria, found to be 39 ± 9 mm and 72 ± 17 mm in this study, were identified as the most critical geometries for successful TAH connection. This geometric constraint restricts the maximum separation allowable between left and right inlet ports of a TAH to ensure successful alignment within the available atrial circumference.